2017
DOI: 10.4293/jsls.2016.00106
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Rectopexy with Urinary Bladder Xenograft Reinforcement

Abstract: Background and Objectives:Rectal prolapse is often repaired laparoscopically, frequently with the use of reinforcement material. Both synthetic and biologically derived materials reduce recurrence rate compared to primary suture repair. Synthetic mesh introduces potential complications such as mesh erosion, fibrosis, and infection. Urinary bladder matrix (UBM) represents a biologically derived material for reinforcement of rectal prolapse repair with the potential to improve durability without risks of synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The results of this study for UBM shed light on, and support, clinical publications that have also shown successful outcomes when using UBM surgical devices in the reinforcement of various hernia repairs [50][51][52][53][54]. In combination, these studies suggest that UBM devices present a low risk of complications in the immediate post-operative period due to the timing of resorption, while the long-term recurrence rates appear to be relatively low, suggesting that robust connective tissue replaces the UBM as it is resorbed.…”
Section: Discussionsupporting
confidence: 74%
“…The results of this study for UBM shed light on, and support, clinical publications that have also shown successful outcomes when using UBM surgical devices in the reinforcement of various hernia repairs [50][51][52][53][54]. In combination, these studies suggest that UBM devices present a low risk of complications in the immediate post-operative period due to the timing of resorption, while the long-term recurrence rates appear to be relatively low, suggesting that robust connective tissue replaces the UBM as it is resorbed.…”
Section: Discussionsupporting
confidence: 74%
“…Clinical case studies that utilized commercialized versions of MatriStem UBM™ for wound management (i.e., Cytal R Wound Matrix and MicroMatrix R ; ACell Inc., MD, USA) have also shown that UBM can support deposition of granulation tissue and re-epithelialization in a variety of challenging applications, such as complex traumatic wounds, contaminated wounds and wounds with exposed avascular structures [25][26][27]. Similarly, there is growing evidence for the successful clinical use of UBM in various surgical reinforcement applications [28,29].…”
mentioning
confidence: 99%
“…UBM has demonstrated effectiveness in a variety of anatomic settings in humans including hiatal hernia repair, rectal prolapse repair, esophageal wall repair, and abdominal wall repair [ 16 , 17 , 27 ]. While UBM undergoes a biodegradation process, it is believed that site-appropriate tissue is deposited and remodels to support the local physiologic loads as the UBM device is resorbed.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports of successful reinforcement of fascial defects in humans using UBM have provided anecdotal evidence that the remodeling process may result in the deposition of site-appropriate tissue that may provide sufficient strength and durability as to render the fascial defect effectively repaired and successfully avert further surgery. UBM reinforcement has proven durable in parastomal hernia repair, rectal prolapse repair, and hiatal hernia repair with follow-up ranging from 24 to 36 months on average [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%